2010
DOI: 10.1247/csf.09016
|View full text |Cite
|
Sign up to set email alerts
|

NDP Kinase 7 Is a Conserved Microtubule-Binding Protein Preferentially Expressed in Ciliated Cells

Abstract: ABSTRACT. Nucleoside diphosphate (NDP) kinase is an enzyme that synthesizes the nucleoside triphosphates. In mammals, nine sequences (NDK1-NDK9) have been found with domain(s) homologous to the catalytic domain of NDP kinase, and some of them have been shown to associate with sperm flagella. The present study examines the localization of NDK7, for which little information has been available. Database analysis showed that the NDK7 gene is present in organisms with cilia and flagella. Western blotting analyses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…This fruitful approach has shed light on evolutionary conserved mechanisms involved in Alzheimer's disease [15], ciliary function [24], or epithelial integrity [25]. Nevertheless, the need for studies of Nme functions in non-vertebrate model species was recently stressed by the scientific community [16].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This fruitful approach has shed light on evolutionary conserved mechanisms involved in Alzheimer's disease [15], ciliary function [24], or epithelial integrity [25]. Nevertheless, the need for studies of Nme functions in non-vertebrate model species was recently stressed by the scientific community [16].…”
Section: Resultsmentioning
confidence: 99%
“…They have been shown to play critical roles in spermatogenesis [33][35], sperm motility [2], development [36], and human conditions associated with primary ciliary dyskinesia [37]. The existence of orthologs in non-metazoan species was however unsuspected with the exception of the report of Nme7 in C. reinhardtii and T. thermophila [24]. In the present study, we have demonstrated that Nme5 , Nme6 , Nme7 , and Nme8 genes were present in the metazoan ancestor, while Nme5 , Nme6 , and Nme7 were most likely present in the eukaryote ancestor.…”
Section: Resultsmentioning
confidence: 99%
“…Candidate cTuRC subunit; NDP kinase with function in motile cilia, the role in cTuRC is unknown (Choi et al, 2010;Hutchins et al, 2010;Ikeda, 2010;Teixido-Travesa et al, 2010;Vogel et al, 2010) LGALS3BP…”
Section: Nme7mentioning
confidence: 99%
“…These proteins are associated with microtubules in vivo (in the case of NME5) or able to bind to microtubules in vitro (in the cases of NME7, NME8, and NME9) (Munier et al 2003;Sadek et al 2003;Duriez et al 2007;Ikeda 2010). Deficient ciliar/flagellar motility is associated with Kartagener syndrome, characterized by situs inversus, bronchiectasis, and sinusitis (Kartagener and Horlacher 1936) as well as other symptoms more generally defined as primary ciliary dyskinesia (Marshall 2008).…”
Section: Knockout Mouse Modelsmentioning
confidence: 99%